A role for startups in unleashing the disruptive power of social media. Issue 6 (December 2016) - Ghezzi, Antonio; Gastaldi, Luca; Lettieri, Emanuele; Martini, Antonella; Corso, Mariano
Highlights: Literature has paid little attention to new sources of social media innovation. Analyzing social media startups helps drawing the field's innovation paths. Social media startups are more focused on pure social network services. Social media management is emerging as key area for social media startups. Social media startups often develop open innovation relations with incumbents. Abstract: As social media attract increasing attention from executives and find varied applications in different industries, research on the subject has been investigating the antecedents, moderators, mediators and outcomes of social media adoption, as well as impacts on the organizational and individual level. However, relatively little attention has been paid to the discussion of the new sources of social media innovation—i.e., the upstream originators of social media solutions. Such innovations of a possibly disruptive nature often originate from startups, which can constitute a significant driver for social media development and can influence the adopting incumbents' behaviors. This study aims at shedding first light on social media-based solutions developed and delivered by startups. By surveying the Crunchbase database, we identified 724 funded social media startups, which were further classified into six categories, namely: (i) social network; (ii) social commerce; (iii) social recruitment; (iv) social management; (v) social loyalty and advocacy; (vi) contact management. Our findings show how the large majority of startups deliver social network solutions to incumbents, followed by social media management applications. The findings also shed light on emerging approaches to value generation and open innovation from social media related to and driven by startups.